PENGARUH BUDAYA INGGRIS RAYA DALAM DESAIN MONSTER DAN WORLD BUILDING GAME “POKEMON SWORD” DAN “POKEMON SHIELD” - Nabila Husna Al'Arifah; Dianing Ratri; Irfansyah Irfansyah (Wimba : Jurnal Komunikasi Visual, 2022)
Pokemon Sword and Pokemon Shield is a pair of Role Playing Game (RPG) that were released for Nintendo Switch Console. Pokemon itself is known as the monster collecting game, as their slogan, "Gotta Catch 'Em All". Pokemon is also known for its world which takes visual references from certain regions in the real world, for example, Pokemon X and Pokemon Y are based on French, and Pokemon Sun and Pokemon Moon are based on Hawaii. As for Pokemon Sword and Pokemon Shield, they are based on the United Kingdom. This research will be examined by using the Matrix Manga theory and Building Imaginary World theory to gain an understanding of the visual approach considered by the creators of this game in creating a United Kingdom atmosphere. It is hoped that this research can be used as a reference in world building and its monsters to create a specific atmosphere based on real life place and phenomenon.